Motivation and Care-Concentration in Footballers. Review of Studies - González Campos, G.; Valdivia-Moral, P.; Cachón Zagalaz, J.; Romero Ramos, O. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The study of psychological variables leads to understand the relationship between sport performance and the sportsman. This study stress motivation and attention-concentration in the footballer. The aim is to depend the main scientific research on the two psychological skills. It is Review of primary and secondary sources such as articles, dissertations and books are used. The method used is the analysis and review of the literature. Several studies which analysed some of the psychological variables studied in this population are available. In conclusion, we can emphasize that psychological skills sport performance, and that the front and midfielders have a higher motivation than other players.